2023
DOI: 10.1088/1361-665x/acdcd7
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal origami shape memory metamaterials undergoing compression–twist coupling

Abstract: As origami structures display designable and predictable folding or unfolding shape changes, the origami-inspired mechanical metamaterials have recently been extensively investigated for applications in metamaterial engineering. There were many previous studies on the conventional hexagonal Kresling origami structures, however, there are many issues such as structural optimizations and designable strategies for the mechanical metamaterials, which have not been solved. To solve these issues, in this study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In our previous study [41], we found that the Kresling units present compression-twist coupling during the axial compression, and the axial stress values with the opposite chirality show no differences, whereas the torsional angles are opposite. Based on this result, we studied the differences between homochiral and antichiral unit connections.…”
Section: Module Analysismentioning
confidence: 71%
See 2 more Smart Citations
“…In our previous study [41], we found that the Kresling units present compression-twist coupling during the axial compression, and the axial stress values with the opposite chirality show no differences, whereas the torsional angles are opposite. Based on this result, we studied the differences between homochiral and antichiral unit connections.…”
Section: Module Analysismentioning
confidence: 71%
“…Figure 11(a) shows the stress-strain curves under an axial compression, where the octagonal modules (8-pppp, 8-ppnn, and 8-pnpn) exhibit high stress and smooth curves. Due to the same stress in the unit with different chirality cases [41], the differences on mechanical behaviors of the modules are only influenced by the soft hinges. The quadrilateral modules have shown the lowest peak stresses.…”
Section: Fea Resultsmentioning
confidence: 99%
See 1 more Smart Citation